Pengembangan E-LKPD Berbasis Video Podcast pada Materi Protista Kelas X di SMA Negeri 2 Gowa - Hasrul, Hasrul; Hamansah, Hamansah; Syamsul, Syamsul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study discusses the development of video podcast-based e-LKPD on class X protist material at SMA Negeri 2 Gowa with the aim of finding out the steps to develop, validity, and practicality of video podcast-based e-LKPD. The instruments used are validation sheets, questionnaires, and learning outcome tests that have been validated. The analysis technique uses data analysis for validity, practicality, and effectiveness. The result of the validity level of e-LKPD is 3.87 with a very valid category. The level of practicality of e-LKPD is 3.36 with the category of very practical. This study obtained results with scores above the KKM standard (100%) in the effective category. The implication of this research is that for educators, it can develop a variety of learning teaching materials to achieve learning goals and support the sustainability of the learning process in the classroom. For researchers, it is better to be able to develop a video-based e-LKPD that is more interesting both in terms of appearance and content of the e-LKPD. For future researchers, it is recommended that the images displayed in the e-LKPD based on the podcast video can be further created and implemented on a large scale.